The Influence of the Informal Economy on the Growth Rate of Real GDP within the Association of Southeast Asian Nations - Eng, Ratana; Lim, Siphat (International Journal of Economics and Financial Issues, 2025)
The assessment of the informal economy’s impact on economic growth in the Association of Southeast Asian Nations (ASEAN) member states was carried out using three different static panel data models: pooled Ordinary Least Squares (OLS), random effects, and fixed effects models. This comprehensive study covered a period of twenty-seven years and included ten countries, yielding a total of 270 observations. The estimated coefficient for the informal economy in the random effects model was 0.0780, while in the fixed effects model it was 0.1747, both of which were statistically significant at the 5% level. These results indicated that an increase in the formal economy would contribute positively to real GDP growth in the ASEAN member states. Additionally, both panel data models revealed that the inflation rate significantly affected real GDP, although the estimated coefficients were negative, with values of -0.0723 for the RE model and -0.0995 for the FE model, both significant at the 1% level. Conversely, the research did not find a significant relationship between population growth rate and real GDP. Notably, there was no significant correlation between any of the variables and real GDP when analyzed under the OLS model.